Artificial intelligence literacy in higher and adult education: A scoping literature review - Laupichler, Matthias Carl; Aster, Alexandra; Schirch, Jana; Raupach, Tobias (Computers and education. Artificial intelligence, 2022)
Since artificial intelligence (AI) is finding its way into more and more areas of everyday life, improving the AI skills of non-experts is important and will become even more relevant in the future. While it is necessary that children learn about the possibilities of AI at an early age, adults in higher education and beyond should also have at least a basic understanding of AI (i.e., AI literacy) to be able to interact effectively with the technology. To evaluate the current state of the literature on AI literacy in higher and adult education, a scoping literature review was conducted with the objective of identifying thematic foci and recent research trends. Ten research databases were searched and out of 902 initial records, 30 studies were identified using predefined eligibility criteria, whereof the content was evaluated in the review. The results indicated that research in this area is still in its infancy and needs refinement in terms of how to define AI literacy in adult education as well as what content should be taught to non-experts. Lastly, several recommendations for research and practice are derived from the results. •Identifies 30 studies in the research area “AI literacy in higher education”•Lists recurring thematic foci and issues in AI literacy research.•Presents the pedagogical structure of courses intended to foster AI literacy.•Calls for more research on AI literacy training and validated assessment scales.